Hope and anticipation in education for a sustainable future. (November 2017) - Ojala, Maria
Highlights: Researchers argue that there is a need of including anticipatory emotions, such a hope, in education for sustainable development (ESD). But is hope a source of engagement or just an illusory feeling? Theories about hope and studies about young people and hope in relation to climate change are reviewed critically. The review shows that hope is a multifaceted concept consisting of emotional, cognitive, and action components, and serving different functions and being based in different sources. If hope is going to work in a transformative way it is argued that it is vital to promote critical emotional awareness and trustful relationships in the ESD classroom. Abstract: Global sustainability problems pose serious challenges for humanity. In handling these problems education for sustainable development (ESD) is seen as important. Different key competences that ESD should focus on have been introduced, such as the ability to deal with future dimensions. Still, studies indicate that future dimensions are not always included in ESD and that many young people are pessimistic concerning the global future. Therefore, one could argue that a focus on anticipatory emotions, especially hope, should be included in ESD. There is a worry, however, that hope will lead to unrealistic optimism and/or less engagement. The aim of this paper is to problematize the discussion about hope in relation to ESD and the global future by grounding it in theories from different disciplines and in empirical research about young people, hope, and climate change. The review shows that hope is a complex, multifaceted, and sometimes contested concept. Hope can be related to denial, but in other cases it can help people face and do something constructive with their worries about the global future. The close relation between hope and trust is emphasized and a need for critical emotional awareness in ESD is argued for.